Mechanistic Complexity of Asymmetric Transfer Hydrogenation with Simple Mn-Diamine Catalysts - van Putten, Robbert (Organometallics, 2019)
The catalytic asymmetric transfer hydrogenation (ATH) of ketones is a powerful methodology for the practical and efficient installation of chiral centers. Herein, we describe the synthesis, characterization, and catalytic application of a series of manganese complexes bearing simple chiral diamine ligands. We performed an extensive experimental and computational mechanistic study and present the first detailed experimental kinetic study of Mn-catalyzed ATH. We demonstrate that conventional mechanistic approaches toward catalyst optimization fail and how apparently different precatalysts lead to identical intermediates and thus catalytic performance. Ultimately, the Mn-N,N complexes under study enable quantitative ATH of acetophenones to the corresponding chiral alcohols with 75-87% ee